Low Diastolic Blood Pressure as a Risk for All-Cause Mortality in VA Patients - Steven Tringali; Charles William Oberer; Jian Huang (International Journal of Hypertension)
Background. A paradoxical increase in cardiovascular events has been reported with intensively lowering diastolic blood pressure (DBP). This J-curve phenomenon has challenged the aggressive lowering of blood pressure, especially in patients with coronary artery disease. Objective. Our objective was to study the effects of low DBP on mortality and determine a threshold for which DBP should not be lowered beyond. Methods. We evaluated a two-year cross-section of primary care veteran patients, from 45 to 85 years of age. Receiver operating characteristics (ROC) were employed to establish an optimal cut-off point for DBP. Propensity-score matching and multivariate logistic regression were used to control for confounders. All-cause mortality was the primary outcome. Results. 14,270 patients were studied. An ROC curve found a threshold value of DBP 70 mmHg had the greatest association with mortality (P<0.001). 49% of patients had a DBP of 70 mmHg or less. Using a propensity-matched multivariate logistic regression, odds ratio for all-cause mortality in subjects with a DBP less than 70 mmHg was 1.5 (95% CI 1.3–1.8). Conclusions. Reduction of DBP below 70 mmHg is associated with increased all-cause mortality. Hypertension guidelines should include a minimum blood pressure target.